(untitled) (CODESRIA Bulletin, 2020)
In this issue Editorial ———————-1 1. Pop Developmentalism in Africa, Grieve Chelwa ———–3 2. Involuntary Social Experimentation: Revisiting the Case for a Moratorium, Nimi Hoffmann ————–7 3. Randomised Trials as a Dead-end for African Development, Seán M. Muller ————————–14 4. Climate Services for Smallholder Farmers Using Mobile Phones: Evidence from a Pilot Randomised Controlled Trial in North Benin, Rosaine N. Yegbemey ——-21 5. Trust, Legitimacy and Community Perceptions on Randomisation of Cash Transfers, Marion Ouma ————25